Effect of obesity on perioperative outcomes following lung cancer surgery: a systematic review and meta-analysis - Wang, Qiuxiang; Li, Zhishu; Wang, Xi Huan; Li, Bin; Wang, Chunfeng; Xiang, Yongguo (Frontiers in Oncology, 2025)
BackgroundThis meta-analysis systematically evaluated the impact of obesity on perioperative outcomes in patients undergoing lung cancer surgery to provide robust evidence for clinical decision-making and patient management.MethodsA systematic review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Comprehensive searches were performed across PubMed, Embase, The Cochrane Library, Web of Science, and Medline. A random-effects model was employed, and the meta-analysis was conducted using Stata software (version 16.0).ResultsEighteen studies comprising 88,413 participants were included in the meta-analysis. Postoperative mortality was significantly lower in the obese group (odds ratio [OR]: 0.73; 95% confidence interval [CI]: 0.59–0.90; P = 0.003). Statistically non-significant differences were observed between the two groups regarding postoperative complications (OR: 1.14; 95% CI: 0.71–1.84; P = 0.582), pulmonary complications (OR: 1.21; 95% CI: 0.57–2.58; P = 0.621), cardiovascular complications (OR: 1.54; 95% CI: 0.86–2.76, P = 0.150), and the total hospital stays (standardized mean difference [SMD]: −0.00; 95% CI: −0.17 to 0.17; P = 0.995). However, operation time was significantly longer in the obese group (SMD: 0.18; 95% CI: 0.11–0.26; P < 0.001).ConclusionThe obesity paradox may exist in patients undergoing lung cancer surgery. Although obesity is associated with longer operation duration, it neither increases the risk of complications nor prolongs hospital stays and is generally linked to reduced postoperative mortality.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025648330, identifier CRD42025648330